2000
DOI: 10.1017/s003118209900654x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and distribution of lead in the archiacanthocephalan Moniliformis moniliformis from experimentally infected rats

Abstract: It recently became clear that adult eo- and palaeacanthocephalans parasitizing fish can bioconcentrate several heavy metals to significantly higher concentrations than the tissues of their definitive hosts. Following this discovery the lead accumulation of the archiacanthocephalan Moniliformis moniliformis was investigated using experimentally infected male Wistar rats of the CD-M-strain. The worms were allowed to grow up for 4 weeks post-infection followed by a 3 weeks oral lead exposure of the rats. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…In our study, the bioaccumulation factors obtained for R. rattus/M. moniliformis are in line with those obtained experimentally by Sures et al (2000b), thus supporting the suitability of this system as a useful and promising tool in environmental monitoring.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the bioaccumulation factors obtained for R. rattus/M. moniliformis are in line with those obtained experimentally by Sures et al (2000b), thus supporting the suitability of this system as a useful and promising tool in environmental monitoring.…”
Section: Discussionsupporting
confidence: 87%
“…The scarce information available on terrestrial habitats contributes to the increasing need for further studies on sentinel organisms reflecting small-scale differences in heavy metal pollution in terrestrial ecosystems. In this context, two acanthocephalans, Macracanthorhynchus hirudinaceus from naturally infected pigs in Bolivia (Sures et al 2000a) and Moniliformis moniliformis parasitizing rats in experimental conditions (Scheef et al 2000;Sures et al 2000b), were shown to be important accumulation indicators of some heavy metals (cadmium and lead). Nevertheless, neither acanthocephalan should be considered a good sentinel due to the restricted range of the definitive hosts of M. hirudinaceus and because of the low abundance of M. moniliformis in naturally infected rats.…”
Section: Introductionmentioning
confidence: 99%
“…In the study it was conclusively shown that infection of chub (Leuciscus cephalus) with Pomphorhynchus laevis resulted in significantly lower lead concentrations in the intestine of infected fish compared to uninfected controls. On the other hand, in an experimental study on the lead uptake by Moniliformis moniliformis no reduction of the lead concentration in the kidneys of the rat was observed (Sures et al 2000b).…”
Section: Discussionmentioning
confidence: 89%